A critical view on the book "Rhetoric (1)" published by payame noor university - Ali Reza Shabanlu (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Semantics examines the effective ways of language application, and rhetoricians try to teach the eloquence skills to others and perceive the mystery of the eloquent speech by extracting the effective principles of utterance. The premise of Persian Dari rhetoric books is based on the translation of Arabic rhetorical books with several inserted Persian examples, and has long been quoted the same as a few frequent old examples of the deceased, which indicates that the authors do not properly understand the rhetoric. In this article, the book "Rhetoric 1 (semantics)", which is the textbook of the largest university in the country, Payame Noor, was criticized and evaluated in terms of form, content, methodology and theory. Among the merits of the book, it is possible to mention the topics of semantics on the basis of the Persian grammar categories. Among its defects, it is possible to mention the imposition of the rules of Arabic rhetoric on Persian language, the disregard for the dynamics of language, the appropriation of semantics to literary language, the old black or white (biased) attitude towards Rhetoric, lack of attention to the work’s wholeness and inattentiveness to the oral and auditory aspects of language.